Fiscal Monitor, April 2016 : Acting Now, Acting Together. (Fiscal Monitor; Fiscal Monitor ;, 2016)
The global economy remains fragile at this time. While the recovery in advanced economies is softening, many emerging market and developing economies have experienced a significant economic slowdown, and some large countries show signs of distress. Global risk aversion has risen, and commodity prices have continued to fall since the April 2015 Fiscal Monitor. The weaker outlook and concerns about the ability of policymakers to provide an adequate and swift policy response have amplified downward risks and clouded global prospects. According to this issue of the Fiscal Monitor, the challenging environment calls for a comprehensive policy response to boost growth and reduce vulnerabilities. In particular, it is critical to identify policies that could lift productivity growth by promoting innovation. Fiscal policy can play an important role in stimulating innovation through its effects on research and development, entrepreneurship, and technology transfer.